UTILIZING GOOGLE FORM TO FACILITATE EVALUATION PROCESS OF THE ONLINE LEARNING - Saputri, Mawarni; Nurulwati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This study aims to describe the effectiveness of using Google Forms to facilitate the process of evaluating student learning outcomes in online learning. The research method used is descriptive analytical method with data collection techniques in the form of questionnaires and documentation studies. The subjects of this study were physics and science teachers in the city of Sabang. The procedure for developing evaluations in the learning process using Google Form starts from the stages of planning, creating, publishing and providing instructions for use. The results showed that the understanding, skills and attitudes of teachers after receiving training related to the use of google form as a whole were in the good category. The teacher's response to the use of Google Forms as an alternative evaluation tool in the learning process shows a good response, namely providing good benefits for teachers and students, especially during the COVID-19 pandemic where learning cannot be done face-to-face but online.